The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s12603-010-0008-y
|View full text |Cite
|
Sign up to set email alerts
|

Lower fluid and fruits / vegetable intake in questionable dementia among older Hong Kong Chinese

Abstract: Older people with questionable dementia have lower intakes of vegetables, fruits and fluid than those who were cognitively normal. This may pose additional health risks, and increase their chance of progressing into dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Of the 359 citations identified from database searches, nine articles met the inclusion criteria and were included in the meta-analysis, including five cohort studies ( Barberger-Gateau et al, 2007 ; Vercambre et al, 2009 ; Hughes et al, 2010 ; Ritchie et al, 2010 ; Chen et al, 2012 ) and four cross-sectional studies ( Lee et al, 2010 ; Roberts et al, 2010 ; Wu et al, 2011 ; Chan et al, 2013 ). The study selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 359 citations identified from database searches, nine articles met the inclusion criteria and were included in the meta-analysis, including five cohort studies ( Barberger-Gateau et al, 2007 ; Vercambre et al, 2009 ; Hughes et al, 2010 ; Ritchie et al, 2010 ; Chen et al, 2012 ) and four cross-sectional studies ( Lee et al, 2010 ; Roberts et al, 2010 ; Wu et al, 2011 ; Chan et al, 2013 ). The study selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between greater intake of vegetables and fruits and fish and better cognitive status is suggestive but not completely consistent. Better cognitive function or slow cognitive decline was associated with consumption of fish and vegetables and fruits (Kang et al ., ; Morris et al ., ; Lee et al ., ; Roberts et al ., ; Vizuete et al ., ). However, a study of 13,388 women found no association between total fruit intake and cognitive function (Kang et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…Altogether, 39 subjects were excluded according the above exclusion criteria. Totally 298 T2D patients completed Mini-Mental State Examination (MMSE) [18] and a short memory questionnaire [19]. Sixty-three T2D patients with MCI were detected as cases.…”
Section: Methodsmentioning
confidence: 99%